2001
DOI: 10.4269/ajtmh.2001.65.184
|View full text |Cite
|
Sign up to set email alerts
|

Community-based ivermectin therapy for onchocerciasis: comparison of three methods of dose assessment.

Abstract: Abstract.A new method of assessment based on mid-upper arm circumference (MUAC) is described for dosage adjustment for community-based ivermectin distribution. We studied 878 subjects eligible for ivermectin dosing in Awhum, Nigeria. In a previous preliminary study of 40 persons, MUAC (in cm) correlated with weight (kg) in the first 20 male (r ϭ 0.97, r 2 ϭ 0.95, P Ͻ 0.0001) and the first 20 female subjects (r ϭ 0.94, r 2 ϭ 0.88, P Ͻ 0.0001). We therefore studied the use of height, physical appearance, and MUA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Although only 46.5% individuals would have taken the correct dose with the height assessment, underdosage was extremely limited (0.5% cases), and most cases would have deviated from the correct dose by half tablet. Shu et al [ 11 ] confirmed the good performance of the method proposed by Alexander et al [ 19 ] in relation to the small proportion (3.3%) of underdosage, although overdosage was up to 54%. Shu et al also tested another method of assessment by height, with different dosing levels, which however showed worse performance (21% underdosage).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Although only 46.5% individuals would have taken the correct dose with the height assessment, underdosage was extremely limited (0.5% cases), and most cases would have deviated from the correct dose by half tablet. Shu et al [ 11 ] confirmed the good performance of the method proposed by Alexander et al [ 19 ] in relation to the small proportion (3.3%) of underdosage, although overdosage was up to 54%. Shu et al also tested another method of assessment by height, with different dosing levels, which however showed worse performance (21% underdosage).…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have evaluated the use of height as a proxy for weight for the administration of ivermectin in the context of elimination programs for either onchocerciasis or LF [ 11 , 19 ]. In the early 1990s, Alexander et al [ 19 ] elaborated four dosing intervals corresponding to different heights, for the administration of ivermectin in the context of a placebo-controlled trial for onchocerciasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation